Comparison of intramuscular diclofenac sodium, diclofenac sodium suppository and intravenous tramadol for postoperative analgesia in gynaecological surgeries done under spinal anaesthesia - Khobragade, Sonali Mahendra (International Journal of Research in Medical Sciences, 2018)
Background: Postoperative pain management is a vital factor contributing towards speedy recovery of the patient in the perioperative period without significant morbidity. The purpose of this study was to compare the analgesic efficacy and safety of three most frequently used analgesic drugs-intramuscular diclofenac sodium, diclofenac suppository and intravenous tramadol hydrochloride in patients undergoing gynaecological surgeries. Methods: A hospital based, prospective, randomized, comparative study was undertaken in tertiary care hospital for a period of two years. The study included 90 adult patients undergoing gynaecological surgeries in spinal anaesthesia. Postoperative pain intensity was assessed by visual analogue scale. Level of sedation was assessed by four point scale along with haemodynamics. Results: There were no significant changes in the pulse rate, systolic blood pressure and diastolic blood pressure after giving I.M. diclofenac, diclofenac suppository and I.V. tramadol. The mean VAS scores were comparable in all three groups (p>0.05). The level of sedation was more in tramadol group than in diclofenac intramuscular and rectal group which was statistically significant (p=0.001). Conclusions: Diclofenac suppository provides effective postoperative analgesia when compared with Inj. Diclofenac I.M. and Inj. tramadol I.V. in patients undergoing infraumbilical gynaecological surgeries with stable vitals and no side effects.